Method development and validation for the estimation of metronidazole in tablet dosage form by UV spectroscopy and derivative spectroscopy - K.Narendra reddy; MK.Ranganath (International Journal of Pharmacy and Analytical Research, 2014)
Two simple, precise, rapid, sensitive and accurate spectrophotometric methods have been developed for the estimation of metronidazole in pure form and in tablet dosage form. Metronidazole has absorbance maxima at 313 nm in methanol: water (80:20) for UV spectroscopy and absorbance minima at 298nm for first order derivative spectroscopy. The linearity was obtained and obeyed Beer’s law in the concentration range of 4 - 12 μg/ml and correlation coefficients were 0.9995 and 0.9897 for UV spectroscopy and derivative spectroscopy respectively. The precision values for UV and derivative spectroscopy were found to be 0.35-0.64 and 1.78- 1.92 with mean accuracies 98.60-99.70% and 97.55-103.80% respectively. Limit of detection values for UV and derivative spectroscopy were found to be 0.23 and 1.01 respectively. Limit of quantification for both UV and derivative spectroscopy were found 0.69 and 3.06 respectively. The methods were validated as per the International Conference on Harmonization (ICH) guidelines. The proposed validated methods were successfully used for the quantitative analysis of API and tablet dosage form.